Calorimetric investigations on lithium based ceramics. (December 2021) - Samui, P.; Modi, K.B.; Phapale, S.; Parida, S.C.; Mishra, R.
Highlights: Δ f H °298 of Li2 TiO3, Li2 ZrO3 and LiAlO2 have been measured. Isobaric heat capacity of these compounds has been measured. Thermodynamic functions for Li2 TiO3, Li2 ZrO3 and LiAlO2 have been derived. The observed data has been compared with the literature values. Abstract: Lithium based ceramics namely lithium titanate, lithium zirconate, and lithium aluminate are proposed materials for tritium breeding in a D-T based fusion reactor. Thermodynamic stability of these materials is important for their use under extreme conditions. In this paper, the thermodynamic stability analysis of lithium titanate, lithium zirconate, and lithium aluminate ceramics is reported. The standard molar enthalpy of formation Li2 TiO3 (s), Li2 ZrO3 (s), and LiAlO2 (s) compounds have been determined for the first time employing an isoperibol room temperature solution calorimeter. The standard molar enthalpy of formation of Li2 TiO3 (s), Li2 ZrO3 (s), and LiAlO2 (s) at 298.15 K are found to be – (1632.4 ± 9.7), – (1776.7 ± 6.7), and – (1188.2 ± 5.2) kJ·mol −1, respectively. The isobaric heat capacity of these compounds has been measured over the temperature range 300 K to 770 K employing Differential Scanning Calorimeter (DSC). Using the above experimental results the standard molar Gibbs energy of formation and other thermodynamic functions for these compounds have been derived and compared with the literature values.